Designing a polyvalent vaccine targeting multiple strains of varicella zoster virus using integrated bioinformatics approaches - Amin Rani, Nurul; Moin, Abu Tayab; Patil, Rajesh; Barketullah Robin, Tanjin; Zubair, Talha; Nawal, Nafisa; Sami, Md. Razwan Sardar; Morshed, Md Masud; Zhai, Jingbo; Xue, Mengzhou; Hossain, Mohabbat; Zheng, Chunfu; et al. (Frontiers in Microbiology, 2023)
The Varicella Zoster Virus (VZV) presents a global health challenge due to its dual manifestations of chickenpox and shingles. Despite vaccination efforts, incomplete coverage and waning immunity lead to recurrent infections, especially in aging and immunocompromised individuals.Existing vaccines prevent chickenpox but can trigger shingles reactivation. To address these limitations, we propose a polyvalent multiepitope subunit vaccine targeting key envelope glycoproteins of VZV. Through bioinformatics approaches, we selected six glycoproteins crucial for viral infection. Epitope mapping led to the identification of cytotoxic T lymphocyte (CTL), helper T lymphocyte (HTL), and B cell linear (LBL) epitopes. Incorporating strong immunostimulants, we designed two vaccine constructs, demonstrating high antigenicity, solubility, stability, and compatibility with Toll-like receptors (TLRs). Molecular docking and dynamics simulations underscored the stability and affinity of the vaccine constructs with TLRs.These findings lay the foundation for a comprehensive solution to VZV infections, addressing the challenges of incomplete immunity and shingles reactivation. By employing advanced immunoinformatics and dynamics strategies, we have developed a promising polyvalent multiepitope subunit vaccine candidate, poised to enhance protection against VZV and its associated diseases. Further validation through in vivo studies is crucial to confirm the vaccine's effectiveness and potential to curb VZV spread. This innovative approach not only contributes to VZV control but also offers insights into tailored vaccine design strategies against complex viral pathogens.